Formulation and application of novel bioactive edible coatings to extend storage and shelf life of pomegranate whole fruit and arils - Kawhena, Tatenda Gift (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDAgric)--Stellenbosch University, 2022.